Dystonia associated with carbamazepine toxicity. Issue 682 (August 1982) - Bradbury, A. J.; Bentick, B.; Todd, P. J.
Abstract : An uncommonly reported toxic effect of carbamazepine is a dystonic reaction. We report two children who developed dystonic reactions with toxic serum levels of carbamazepine.